2019
DOI: 10.1186/s13011-019-0208-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of khat price increases on consumption behavior – price elasticity analysis

Abstract: Background The long border of Saudi Arabia with Yemen is the primary route for khat entry to the Kingdom. As of April 2015, the government of SA tightened the border, making it more difficult to import khat into the country. As a result, local user prices of khat probably increased due in part to higher supply costs and perhaps lower quantities. One anti-drug strategy is to increase consumption cost by increasing the price of supply. We aim in this study to measure the responsiveness of khat deman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…One study found that Khat substance is price elastic which means any price change will change the consumption amount, and the relationship was negative. This phenomenon may help the policymakers in the affected countries to control the Khat use habit (73). Similar findings happen when tobacco product prices increase.…”
Section: Khat Usesupporting
confidence: 57%
“…One study found that Khat substance is price elastic which means any price change will change the consumption amount, and the relationship was negative. This phenomenon may help the policymakers in the affected countries to control the Khat use habit (73). Similar findings happen when tobacco product prices increase.…”
Section: Khat Usesupporting
confidence: 57%
“…When asked how much is the cost, interviewees imply that there is a class difference because drugs are too expensive for lower class, particularly after the war with neighbor countries [ 41 ].…”
Section: Ways Of Drug Purchasing In Saudi Arabiamentioning
confidence: 99%
“…Focusing on the demand side of regulation is also worthwhile as khat demand is price elastic (29). This means khat chewers are relatively responsive to price changes.…”
Section: Policy Optionmentioning
confidence: 99%
“…This means khat chewers are relatively responsive to price changes. For example, in one study the price elasticity of khat demand is found to be between − 2.38 and − 1.07, which means that each 1% increase in price is associated with 1-2% reduction in khat quantity demanded [29]. It was also found that one percent increase in the price of khat decreases the amount of money spent for khat consumption by 0.68%.…”
Section: Policy Optionmentioning
confidence: 99%